Upaya Peningkatan Hasil Belajar Dengan Menggunakan Strategi Critical Incident (Pengalaman Penting) Pada Mata Pelajaran Fiqih Siswa Kelas VIII Mts Tarbiyah Waladiyah - Nur Nilam Sari; Anida M; Nurmisda Ramayani (Al-Ulum: Jurnal Pendidikan Islam, 2022)
The objectives of this research are: To find out how the learning outcomes in learning fiqh students of class VIII MTs TarbiyahWaladiyah after using the Critical Incident strategy. This research was conducted in the form of classroom action research. According to the type of research chosen, namely classroom action research, this research uses an action research model in the form of a spiral and from one cycle to the next. The results of this study are: From the student learning outcomes obtained after using the critical incident learning strategy on halal and haram food and beverage materials, it began to increase by 71.87% in the first cycle with 27 students and 93.75% in the first cycle. II with a lot of students 30 students. This shows that the use of critical incident learning strategies on halal and haram food and beverage materials at MTs TarbiyahWaladiyah can improve learning outcomes even more than targeted.